Implementation of E-Government in Improving Public Service Efficiency: A Case Study on the Batu City Government - Hari Purnomo; Suljatmiko Suljatmiko; Ihsan Zikri Ulfiandi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the implementation of e-Government in improving the efficiency of public services in the Batu City Government, especially through the Digital Public Service Mall (MPP)